Analysis Of Risk Management and Profitability: Study on State-owned and Private Banks - Furqoni, Habib Abda; Bukhori, Iskandar; Lorian, Indah Suci; olivia, tasya (Universitas Muhammadiyah Yogyakarta, 2021)
Introduction – The banking sector has a function as a financial channeling institution and financing provider that has a crucial role in society. Therefore, a risk management mechanism is needed to overcome the financial crisis that occurred in 2008. The Government of Indonesia through the Financial Services Authority (Otoritas Jasa Keuangan) issued regulation number 18/POJK.03/2016 concerning Commercial Bank Risk Management which regulates banking risk management. Purpose – This study aims to determine the effect of credit risk, liquidity risk and operational risk on profitability; as well as to determine the differences in the level of credit risk, liquidity risk, operational risk and profitability between state-owned and private banks. Methodology/Approach – This research using multiple regression analysis, data collected from state-owned bank and private banks registered in Indonesian Stock Exchange from 2016 – 2019. Credit risk is proxied by the NPL ratio, liquidity risk is proxied by the LDR ratio, operational risk is proxied by the ROA ratio and profitability is proxied by the ROA ratio mention the method of the research, sampling and data collecting. To determine the difference between state-owned bank and private bank, this research using Mann-Whitney test. Findings – By using multiple linear regression analysis on banks listed on the Indonesia Stock Exchange during 2016-2019, it was found that NPL had a negative effect on ROA, LDR had a positive effect on ROA and BOPO had a negative effect on ROA. In testing the difference, the Mann-Whitney difference test was used which resulted in the finding that there was a difference in the NPL ratio between state-owned and private banks, there was a difference in the BOPO ratio between state-owned and private banks and there was a difference in the ROA ratio between state-owned and private banks. From all different tests, the results show that private-owned banks have worse financial ratios than state-owned banks. Meanwhile, the LDR ratio found that there was no difference between state-owned and private banks. Originality/ Value/ Implication – The results of this study have implications as follow: for banks to pay more attention to the NPL, LDR and BOPO ratios because they affect bank profitability; regulators should pay attention to the financial ratios of private-owned banks in order to control banking risks.